A Educação em direitos humanos nos ambientes escolares e a parceria de Defensores Públicos para seu fomento em tempos de intolerância - Johann, Cristiaine Angelita (Universidade do Vale do Rio dos Sinos, 2023)
This dissertation focuses on human rights education in public basic education schools in the Vale dos Sinos/RS region. It arises from concern about the growth of the discourse of authoritarianism and intolerance from 2018 onwards within Brazilian society, as well as the perception of its democratic fragility. It addresses the challenges for this education and the possibilities for Public Defenders to contribute, through activities developed from a social project. Theoretical references were used that deal with the theme, involving authors from the field of Education, such as Aida da Silva (2010; 2011; 2013); Cláudio Dalbosco (2011; 2021); Gert Biesta (2021); and, Vera Candau (2008; 2012); of Philosophy, Paulo Carbonari (2015; 2019; 2020; 2021); and, from Sociology, Eduardo Bittar (2007; 2008; 2014; 2021) and Theodor Adorno (2020). The research was developed using the participatory research method, of a qualitative and quantitative nature, with analysis of data collected from March to December 2022, based on activities carried out with students from the region and teachers participating in the Laboratory's research and training group in Racial Equality Teaching, from Unisinos. The results indicate the persistence of deep-rooted prejudices and mistaken views regarding the expression human rights and what it represents, the insufficiency of continuing training courses for teachers, highlighting the need for greater government incentives for Education. They also indicate the teachers' fear of this Human Rights Education due to reactions from family members, pointing to the benefit of these activities carried out by Public Defenders in the dimension of awareness, clarification, support and strength. In relation to the students, they indicated a benefit to respecting differences and combating violence, revealing a mistaken view of minors regarding their responsibility for committing illegal acts and a great interest in legal knowledge (from the most diverse areas) that can contribute to the exercise of citizenship. The data justify the need for a paradigmatic change in the work of Public Defenders, which can contribute more directly to human rights education.
Keywords: Educação em direitos humanos; Defensores públicos; Educação básica; Formação continuada; Tempos de intolerância; Human rights education; Public defenders; Basic education; Continuing education; Times of intolerance; ACCNPQ::Ciências Humanas::Educação